Factors of Acute Malnutrition among Under Five Years Children in Northern Bangladesh - Aktar, Mst Shabnaz; Israt, Afsana; Shahrear, Md Ashab; Macsud , Md Anjim (East West Medical College Journal, 2025)
Background: The developmental, medical, economic and social impacts of acute malnutrition in children are serious and long lasting for individuals, families, communities and countries. Malnutrition in childhood damages a child’s both physical and cognitive development and this damage is largely irreversible. These ultimately perpetuate illness, poverty and inequality. Childhood acute malnutrition is multifactorial in origin and majority of them are preventable. Objective: The purpose of this study was to identify the factors of acute malnutrition among under five years children in northern Bangladesh. Methods: This case-control study was carried out in Chapainawabganj general hospitals, Chapainawabganj. Total 180 children aged 6-59 months (90 cases-WHZ < -2 and 90 control-WHZ ≥ -2) were included for this study based on selection criteria. Informed written consent was taken from the guardians of all children. Data were recorded by using a semi-structured questionnaire. Height and weight of children and their parents were measured by measuring tape and weight machine. BMI of children and parents, and weight-for-height Z scores of children were calculated. Collected data were analyzed by the SPSS 23. Chi-squared (ꭓ2) test and unpaired t-test were performed to compare the frequencies and means between the groups. Results: The mean age of the acute malnourished children was 25.84±15.09 months with slight male predominance (male female ratio 1.14:1). The mean weight for height Z score of the cases was -2.93±0.41. Monthly family income <10000 BDT, younger mother (age ≤20 years), younger father (age ≤20 years), less educated mother (Illiterate or upto primary), less educated father (Illiterate or up to primary), undernourished mother (BMI <18.50 kg/m2) and predominant breast feeding stop before 4 months had found to be significantly associated with acute malnourishment (p<0.05). Conclusion: Acute malnutrition was found to be significantly associated with low monthly family income, younger mother and father, less educated mother and father, undernourished mother and early stop of predominant breast feeding. EWMCJ Vol. 13, No. 1, January 2025: 35-42